SISTEM INFORMASI MANAJEMEN PROYEK PADA PERUSAHAAN KONTRAKTOR - Onky Fatur Rahman (Jurnal Riset Teknik Komputer, 2024)
Project management is at the core of a contracting company's operations in the modern construction industry. This study aims to evaluate the impact of implementing the Project Management Information System (SIMPRO) in the context of operational efficiency, competitive ability and regulatory compliance. The research method used is a literature review, which analyzes various sources related to SIMPRO implementation and its effects on contractor companies. The study results show that SIMPRO can increase operational efficiency by providing an integrated platform for managing project data, facilitating fast and appropriate decision making, and strengthening company compliance with regulations and safety standards. Despite facing implementation challenges, the benefits offered by SIMPRO provide a valuable investment for contracting companies in facing an increasingly competitive and dynamic business environment in the construction industry.